1960
DOI: 10.2307/4590775
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Excess Weight in Children and Adults

Abstract: Overweight children usually become overweight adults9 according to a study, spanning 20 years, of 200 residents of Hagerstown, Md.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
39
0
5

Year Published

1962
1962
2002
2002

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 205 publications
(46 citation statements)
references
References 12 publications
2
39
0
5
Order By: Relevance
“…If the prevalence of obesity continues to grow, the disease burden will surely increase further. As overweight children become overweight adults, [21][22][23][24][25][26] the diseases associated with obesity and health care costs are likely to increase even more. Because disproportionate weight gains have occurred among heavier children, 2 the rate of obesityassociated diseases will rise even faster if the expanding prevalence of obesity continues.…”
Section: Resultsmentioning
confidence: 99%
“…If the prevalence of obesity continues to grow, the disease burden will surely increase further. As overweight children become overweight adults, [21][22][23][24][25][26] the diseases associated with obesity and health care costs are likely to increase even more. Because disproportionate weight gains have occurred among heavier children, 2 the rate of obesityassociated diseases will rise even faster if the expanding prevalence of obesity continues.…”
Section: Resultsmentioning
confidence: 99%
“…23 In one study, about three-quarters of obese 10 ± 13-yold boys and girls became obese adults, compared with 31% and 11% of non-obese boys and girls; relative risks of 2.39 and 6.55. 24 A study of a birth cohort of the year 1946 25 showed that only 21% of obese (BMI greater than 29.9 kgam 2 ) 36-y-olds had been obese at age 11 y (weight-for-height greater than 120% of a standard weight for children of the same age, height and sex), however the percentage of adult obesity increased to 58% if combining childhood overweight (weight-for-height greater than 110%) and obesity. In another study of birth cohorts from the same period (1929 ± 1960), the odds ratios for Determinants of overweight tracking in children L Mo-suwan et al overweight at 35 y ranged from 3.9 to 8.4 for childhood obesity at 8 ± 13 y of age (BMI values at the 95th percentile relative to 50th percentile).…”
Section: Discussionmentioning
confidence: 99%
“…Infant and childhood obesity have been related to adult obesity (Abraham et al, 1971;Charney et al, 1976). Early obesity seems to place a child at risk for being an overweight adult (Abraham & Norsieck, 1960). Familial relationships contributing obesity have been noted (Hartz et al, 1977), particularly parent/child interrelationships.…”
mentioning
confidence: 97%